When fracking comes to town : governance, planning, and economic impacts of the US shale boom - Deitrick, Sabina E. 1957-; Murtazashvili, Ilia, 1975- (Cornell University Press, 2021)
"This book considers how planners and local public administrators responded to the natural gas shale boom, declining shale production, and the local economic consequences of fracking. Rather than powerlessness, the case studies show how communities adapted to new challenges while capturing some of the economic benefits from the fracking revolution"--